Identification of Novel Peptide Antagonists for von Willebrand Factor Binding to the Platelet Glycoprotein Ib Receptor from a Phage Epitope Library - Ricca, George A; South, Victoria; Searfoss, George H; French, Stephen; Cheadle, Christopher; Murray, Edward; Howk, Richard; Jaye, Michael (Thrombosis and Haemostasis, 1995)
We have constructed a fusion phage epitope library in the filamentous bacteriophage fuse5. The library was made by inserting a degenerate oligonucleotide which encodes 15 variable amino acids into the NH2-terminal region of the phage gene III protein. This library, containing over 107different epitope bearing phage, has been used in an attempt to identify inhibitors of the von Willebrand factor (vWF)-platelet Glycoprotein lb interaction. The library was screened with a monoclonal antibody (RG46) that recognizes the GPIb binding domain of vWF (amino acids 445-733). A total of 30 clones falling into 8 classes have been identified that react with the RG46 antibody. Isolates from all 8 classes are positive by immunoblot analysis. The amino acid sequence of the gene III fusion protein from positive clones showed a strong homology to the known RG46 epitope. Peptides identified from the screen were synthesized and used to demonstrate that some of the synthetic peptides exhibited inhibitory activity towards ristocetin induced binding of vWF to the GPIb receptor. Thus, we have demonstrated that screening a fusion phage epitope library with a monoclonal antibody that inhibits vWF binding to the GPIb receptor can be a useful tool not only for mapping antibody recognizing determinants, but also can serve as a source for identifying novel peptides that are antagonists for vWF binding to the platelet GPIb receptor.